2017
DOI: 10.1128/microbiolspec.funk-0046-2016
|View full text |Cite
|
Sign up to set email alerts
|

Fungal Sex: The Basidiomycota

Abstract: SUMMARY Fungi of the Basidiomycota, representing major pathogen lineages and mushroom-forming species, exhibit diverse means to achieve sexual reproduction, with particularly varied mechanisms to determine compatibilities of haploid mating partners. For species that require mating between distinct genotypes, discrimination is usually based on both the reciprocal exchange of diffusible mating pheromones, rather than sexes, and the interactions of homeodomain protein signals after cell fusion. Both compatibility… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
155
1
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 97 publications
(160 citation statements)
references
References 201 publications
(267 reference statements)
2
155
1
2
Order By: Relevance
“…In basidiomycetes, mating type is typically controlled by two loci: (i) the pheromone receptor (PR) locus, which carries one gene encoding a mating-type-specific PR and one to several genes encoding pheromones, and (ii) the homeodomain gene (HD) locus, encoding two homeodomaintype transcription factors controlling postmating growth. Recombination suppression ensures full linkage of the mating-type genes within each of these two loci, which is required for correct mating-type determination (11), and typically does not extend beyond the mating-type genes (12,13). Recombination suppression…”
mentioning
confidence: 99%
“…In basidiomycetes, mating type is typically controlled by two loci: (i) the pheromone receptor (PR) locus, which carries one gene encoding a mating-type-specific PR and one to several genes encoding pheromones, and (ii) the homeodomain gene (HD) locus, encoding two homeodomaintype transcription factors controlling postmating growth. Recombination suppression ensures full linkage of the mating-type genes within each of these two loci, which is required for correct mating-type determination (11), and typically does not extend beyond the mating-type genes (12,13). Recombination suppression…”
mentioning
confidence: 99%
“…Yet, knowledge about export of pheromones from the Basidiomycetes class is scarce and somewhat contradictory. Though all pheromones of this class are stated to be diffusible [122], radiolabeling of tremerogen A-10, the mating factor of the heterobasidiomycetous yeast Tremella mesenterica, showed that it initially appeared in a membranebound form and subsequently converted into a more soluble form prior to secretion, suggesting a more complex form of transport [123]. Furthermore, basidiomycete pheromones all carry CaaX motifs for Cterminal farnesylation, which in turn aids membrane localization, guiding the pheromone to a transmembrane transporter protein [124,125].…”
Section: Communication Through Hydrophobic Moleculesmentioning
confidence: 99%
“…Among the Tremellomycetes, pathogenic Cryptococci are so far the only species for which fused MAT loci have been described [17,23]. In a previous study, we analyzed the genome sequence of Cutaneotrichosporon oleaginosum strain IBC0246 (formerly Trichosporon oleaginosus), which belongs to the Trichosporonales, a sister order to the Tremellales within the Tremellomycetes class.…”
Section: Amylolentus Kwoniella Heveanensis Kwoniella Mangrovensis mentioning
confidence: 99%
“…One MAT locus usually contains tightly linked pheromone and pheromone receptor genes (P/R locus) involved in premating recognition, and the other encodes homeodomain transcription factor genes encoding homeodomain (HD) proteins of class 1 and class 2 (HD locus) determining viability after syngamy. Importantly, alleles at both loci must differ between mating partners for completion of the sexual cycle [17].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation